2006
DOI: 10.1590/s0103-50532006000700038
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II) chloride-mediated synthesis of beta-enamino compounds under solvent-free conditions

Abstract: Uma variedade de β-enaminonas e β-enamino ésteres foi sintetizada pela reação de compostos 1,3-dicarbonílicos com aminas na presença de quantidade catalítica de cloreto de cobalto(II), à temperatura ambiente na ausência de solventes. O procedimento experimental é simples e os produtos são isolados em altos rendimentos.A variety of β-enaminones and β-enamino esters can be synthesized by the reaction of 1,3-dicarbonyl compounds with amines in the presence of a catalytic amount of cobalt(II) chloride at room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 19 publications
2
19
0
1
Order By: Relevance
“…The direct enamination of 1,3-dicarbonyl compounds with amines is one of the most straightforward methods for the synthesis of β-enamino ketones and esters in the presence of various promoting agents. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Recent reports have described the preparation of β-enamino ketones and esters catalyzed by metal triflate. 20 Although the reported methodologies are suitable for certain synthetic conditions, some of these procedures suffered from disadvantages, such as long reaction time, low yield, use of volatile organic solvents, requirement of excess of reagents or costly catalysts, special apparatus and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The direct enamination of 1,3-dicarbonyl compounds with amines is one of the most straightforward methods for the synthesis of β-enamino ketones and esters in the presence of various promoting agents. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Recent reports have described the preparation of β-enamino ketones and esters catalyzed by metal triflate. 20 Although the reported methodologies are suitable for certain synthetic conditions, some of these procedures suffered from disadvantages, such as long reaction time, low yield, use of volatile organic solvents, requirement of excess of reagents or costly catalysts, special apparatus and harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…18 Unfortunately, in general, the processes to synthesize trihalomethyl substituted β-enamino ketones suffers from limitations, such as long reaction times, multi-step reactions and tedious work-up. 19,20 Thus, because of the applicability of β-enamino trihalomethyl ketones as a promising building blocks for the synthesis heterocycles, 21,22 a simple, general and high yielding onepot approach for the synthesis of this enaminones is highly desirable. In particular, it has been shown that syntheses which are carried out in solvent-free conditions are often rapid, regio-or chemoselective, occur in high yields and have environmental and economic advantages.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Aliphatic azides are usually prepared by nucleophilic substitution of the corresponding halides or sulfonates by azide ion. [5][6][7][8] Due to the advantageous and attractive strategy of the direct synthesis of azides from alcohols, some limited methods have been developed. Along this line, methods based on Mitsunobu conditions [7][8][9][10][11] are widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Due to the advantageous and attractive strategy of the direct synthesis of azides from alcohols, some limited methods have been developed. Along this line, methods based on Mitsunobu conditions [7][8][9][10][11] are widely applied. These methods utilize reagents such as hydrazoic acid, diphenylphosphoryl azide, the bispyridine complex of zinc azide or the tetrabromocyclohexadienone/Ph 3 P system as the azide source/nucleophilic component.…”
Section: Introductionmentioning
confidence: 99%